(3GdHMQGfs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3Efj dSJ CbUO aj cJGHj gPG Edi Cf CdNU Ydi Cj eYfi jbY GSe GdHMQGf? CYdi GdJZjjQ GdPj jchf aj GdeQV OaYg? Ce Ydi ejd GdeQjV abW Edi GdMGd GdJj gj CUdM? s
(3BNQgG (B:s
(3aef bHd gPg GdJQGcjH hGdJQGhjM EP cGfJ djSJ HGdHjfI ddcKjQ ef GdCWHGA ZdWhG aj CSeGA gPg GdeYGfj, Ke ZdWhG CjVkG eY Pdc aj JYQa faS GdeYGfj s
(3KdGK ebGdGJs
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(2/6400) s
Keywords: (3GdWHs